Peculiarities of sol-gel synthesis of co-modified by nitrogen and metal ions (Zn2+, Zr4+, Pt2+) semiconductive TiO2 films - Linnik, О.P.; Smirnova, N.P.; Eremenko, A.М. (Reports of the National Academy of Sciences of Ukraine, 2020)
According to the XPS investigation of titania films co-modified by nitro gen and metal ions obtained via sol-gel method, the formation of common bonds between elements occurs due to the presence of metal ions. The mechanism of urea thermolysis is changed as a result of the ability of metal ions to form the complex compounds with urea molecules under the reported synthesis conditions that, in turn, depends on the nature of metal ions, leading to the different chemical compositions of materials’ surface. The XPS data show that nitrogen atoms are surrounded by nonmetal ones on the surface of the films modi fied by Zn2+ or Zr4+ ions. It is suggested that no formation of the complexes between Ті, Zn, or Zr atoms with urea occurs due to its protonation through an oxygen atom leading to the formation of O,N-containing reaction products. In the case of Pt2+ doping, the substitutional nitrogen incorporation in the titania lattice, as well as the formation of N-containing fragments, have been detected. The chemical nature of Pt ions allows them to interact with urea molecules through an N atom of the amino group. As a result, the transformation of urea molecules in the complexes occurs at higher temperatures concurrently with the titania crystallization that is recognized as a catalyst for the intermediates of the urea decomposition leading to the formation of common bonds between N and Ti atoms.